Tubakia byeongjinii, a new species of Tubakiaceae, isolated from Quercus variabilis in South Korea - Cho, Sung-Eun; Shin, Keumchul; Kim, Yong-Ho; Lee, Dong-Hyeon (Phytotaxa, 2024)
A routine survey to establish an inventory of fungal pathogens occurring on Quercus spp. in South Korea was conducted in the autumn of 2021 and 2022. Symptoms, including leaf spot, were frequently observed on Quercus variabilis leaves in a natural forest located in Sejong. A fungus with unique morphological characteristics, including pycnothyria, was found to be a major colonizer in the infected leaves of Q. variabilis. Based on the morphological characteristics of the fungus, it was identified as a member of Tubakia. Sequence comparisons of LSU, ITS, and TEF-1α gene regions revealed that the fungus was an undetermined species of Tubakia. This novel species is described as T. byeongjinii sp. nov., and this is the first report of Tubakia species on Q. variabilis in South Korea.